Minister of Youth and Sports met some 1,500 university students and representatives from youth and sports associations in a town hall meeting in UMP - UMP, PNC (2019)
More than 1,500 undergraduates and representatives from youth and sports associations turned up at Astaka Hall in Universiti Malaysia Pahang (UMP) Gambang Campus for a town hall meeting with Minister of Youth and Sports Yang Berhormat Syed Saddiq Syed Abdul Rahman that was held on February 18, 2019.